2013
DOI: 10.1016/j.fitote.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Two new tryptophan derivatives from the seed kernels of Entada rheedei: Effects on cell viability and HIV infectivity

Abstract: Two new tryptophan derivatives, N-sulfonyl-L-tryptophan (tryptorheedei A) (1) and 3-(N-sulfonylindolyl)-D-lactic acid (tryptorheedei B) (2) together with the known 5-O-β-D-glucopyranosyl-2-hydroxyphenylacetic acid (3), 1-O-methylglucopyranoside, entadamide A, homogentisic acid and 3-O-β-D-glucopyranosyl-β-sitosterol, were isolated from the seed kernels of Entada rheedei (Mimosaceae). Their structures were established using 1D and 2D NMR spectroscopy, mass spectrometry and by comparison with spectroscopic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Furthermore, IDO activity causes even more imbalance in the T-cell subsets by increasing the proportion of T-regulatory [193] and decreasing the proportion of T-helper 17 cells [194]. In chronically infected hosts, the dysregulated activation/alterations in the immune regulatory mechanisms involving IDO lead to a compromised antiviral response and enhancement of viral replication [195–197]. In short, chronic IDO activation leads to the immune impairment, whereas IDO inhibition represses viral replication.…”
Section: Ros In Hiv-1 Related Pathologiesmentioning
confidence: 99%
“…Furthermore, IDO activity causes even more imbalance in the T-cell subsets by increasing the proportion of T-regulatory [193] and decreasing the proportion of T-helper 17 cells [194]. In chronically infected hosts, the dysregulated activation/alterations in the immune regulatory mechanisms involving IDO lead to a compromised antiviral response and enhancement of viral replication [195–197]. In short, chronic IDO activation leads to the immune impairment, whereas IDO inhibition represses viral replication.…”
Section: Ros In Hiv-1 Related Pathologiesmentioning
confidence: 99%
“…Previous chemical studies on Sansevieria trifasciata led to the isolation of steroidal sapogenins namely 25S-ruscogenin and sansevierigenin (Gonzalez et al, 1972), pregnane glycosides (Mimaki et al, 1997), and steroidal saponins (Mimaki et al, 1996). As part of our program based on the phytochemical investigation of Cameroonian medicinal plants (Nzowa et al, 2013;Teponno et al, 2013a;Fouedjou et al, 2014;Ponou et al, 2014), we have examined the aerial parts of S. trifasciata growing in Cameroon and this work led to the isolation and structure elucidation of two new sappanin-type homoisoflavonoids. Homoisoflavonoids are a rather uncommon subclass of flavonoids rarely found in nature which contain one additional carbon atom.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies are also noted the phytochemical profile of the Entada species and the phytocompounds are corresponding the pharmacological activities like antimicrobial and antioxidants (Rahman et al, 2013;Nathan, 2017). Nzowa et al, (2013) have been reported the tryptophan derivatives in seed kernel of E. rheedii. The present results are also on par with above investigation that has been enumerated many pyridine and purine compounds in E. pursaetha plant part extract (Tables 1-2).…”
Section: Discussionmentioning
confidence: 99%